Agro-Ecotourism in Ciputri Village: Evaluating Potentials and Strategies for Sustainable Tourism Development - Putri, Inanditya W; Setiadi, Hafid (UI Scholars Hub, 2026)
Sustainable rural tourism development requires integrated planning that balances environmental conservation, community participation, and local economic growth. Agro-ecotourism has emerged as an important approach to support village-based tourism development in environmentally sensitive areas. Ciputri Village in Cianjur Regency has been designated as a tourism village and possesses considerable agro-based and ecological potential. However, tourism development remains suboptimal due to limited public awareness, low visitor numbers, and fragmented strategic planning. This study aims to assess agro-ecotourism potential and to formulate priority development strategies. An integrated approach combining Participatory Geographic Information Systems (P-GIS), SWOT-based EFAS/IFAS analysis, and the Analytic Hierarchy Process (AHP) was applied. Participatory mapping involving five stakeholders identified 11 agro-ecotourism attractions. The results indicate that Ciputri Village is positioned in the Strength–Opportunity quadrant. Environmental and socio-cultural aspects emerged as the highest priorities, and a growth-oriented strategy emphasizing concentration through vertical integration was identified as the most appropriate development approach.